2012
DOI: 10.1097/nnd.0b013e31825515c4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of New Graduate Nurses’ Organizational Commitment During a Nurse Residency Program

Abstract: Retaining newly graduated nurses is critical for organizations because of the significant cost of turnover. Since commitment to an organization is associated with decreased turnover intent, understanding factors that influence new graduates' organizational commitment is important. In a sample of nurse residency program participants, predictors of organizational commitment over time were explored. Perceptions of the work environment, particularly job satisfaction and job stress, were found to be most influentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…In this study, most residents indicated that supplemental classes improved their professional development significantly. This is consistent with evidence found in the nursing literature that educational support for residents such as supplemental classes are considered an important source of success (Bratt, 2009;Bratt & Felzer, 2012;Goode et al, 2009).…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…In this study, most residents indicated that supplemental classes improved their professional development significantly. This is consistent with evidence found in the nursing literature that educational support for residents such as supplemental classes are considered an important source of success (Bratt, 2009;Bratt & Felzer, 2012;Goode et al, 2009).…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…When nurses participate in a formal nurse residency program that focuses on socialization and transitioning into practice, they are more committed to the organization and are more satisfied in their work, which leads to an increased retention rate within an organization (Beauregard, Davis, & Kutash, 2007;Bratt & Felzer, 2012;Newhouse, Hoffman, Sulfita, & Hairston, 2007). Nurse residency programs support nurses as they are socialized into their profession and provide a means of giving frequent and meaningful feedback to new graduates in the first year of practice and beyond (Olson-Sitki, Wendler, & Forbes, 2012).…”
Section: Nurse Residency Programsmentioning
confidence: 99%
“…[29,30] In another study of one-year outcomes of a post-baccalaureate residency program, Williams and colleagues [31] found that participants' job satisfaction improved on study variables such as, professional opportunities and control-responsibility at 12 months. Bratt and colleagues [12] also claimed that perceptions of the work environment particularly job satisfaction and job stress were found to be most influential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[8][9][10] On a grounded theory study, Mellor and Greenhill [11] noted that new nurses in transition to practice reported to have feelings of underprepared for practice, overwhelmed by responsibility, and often abandoned when clinical support did not occur. New graduates' increasing stress level and feelings of incompetence led to a higher potential for turnover [12] which could be detrimental to providing safe patient care in clinical agencies. Kovner, Brewer, Fatehi, and Jun [13] reported that approximately 17.5% of new nurses left their first job within one year of starting their work.…”
Section: Literature Reviewmentioning
confidence: 99%